2005
DOI: 10.1021/ac0508649
|View full text |Cite
|
Sign up to set email alerts
|

Detection of C-Reactive Protein Utilizing Magnetic Permeability Detection Based Immunoassays

Abstract: A new sensing technology platform integrating magnetic permeability detection and a two-site heterogeneous immunoassay in a one-step analysis is described. As a platform model, measurements of C-reactive protein (CRP), a cardiac and inflammation marker, were performed in a rapid (11.5 min) high-sensitivity (hs) procedure with a low detection limit (0.2 mg/L) and accuracy (CV = 11%). The two-site heterogeneous immunoassay was performed in 1.2-mL disposable reagents vials containing solid phase (polyclonal anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…It is classified as a characteristic acute phase reactant in human serum and a classic marker of inflammation (Christodoulides et al, 2005;Kushner and Rzewnicki, 1994;Wolf et al, 2004). Several studies have demonstrated the association between inflammation and cardiovascular disease and testing of serum CRP levels is suggested as a new way of monitoring the risk of cardiac disease (Kriz et al, 2005;Pearson et al, 2003;Ridker and Morrow, 2003). At central hospital locations, high sensitivity CRP (hsCRP) testing is currently performed utilizing turbidimetric or nephelometric homogeneous immunoassays on large clinical analyzers (Kriz et al, 2005;Roberts et al, 2001), and the techniques are very time consuming (response detection time > 12 h) and cannot be used for immediate health assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is classified as a characteristic acute phase reactant in human serum and a classic marker of inflammation (Christodoulides et al, 2005;Kushner and Rzewnicki, 1994;Wolf et al, 2004). Several studies have demonstrated the association between inflammation and cardiovascular disease and testing of serum CRP levels is suggested as a new way of monitoring the risk of cardiac disease (Kriz et al, 2005;Pearson et al, 2003;Ridker and Morrow, 2003). At central hospital locations, high sensitivity CRP (hsCRP) testing is currently performed utilizing turbidimetric or nephelometric homogeneous immunoassays on large clinical analyzers (Kriz et al, 2005;Roberts et al, 2001), and the techniques are very time consuming (response detection time > 12 h) and cannot be used for immediate health assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the association between inflammation and cardiovascular disease and testing of serum CRP levels is suggested as a new way of monitoring the risk of cardiac disease (Kriz et al, 2005;Pearson et al, 2003;Ridker and Morrow, 2003). At central hospital locations, high sensitivity CRP (hsCRP) testing is currently performed utilizing turbidimetric or nephelometric homogeneous immunoassays on large clinical analyzers (Kriz et al, 2005;Roberts et al, 2001), and the techniques are very time consuming (response detection time > 12 h) and cannot be used for immediate health assessment. Moreover, the existing technology cannot be easily translated into a point-of-care device as they require high sample volumes ( > 1 mL) obtained by drawing venous blood with a syringe.…”
Section: Introductionmentioning
confidence: 99%
“…The detection limit for CRP was 0.2 mg/L, and the linear dynamic range was 5-160 mg/L. [13][14] MNPs are composed of Fe 3 O 4 , and thus have lower toxicity and are more biocompatible compared to other NPs. MNPs have also been used as contrast agents for magnetic resonance imaging (MRI) to locate targeted tissues for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are several advancements for measuring CRP has been reported. For example, a CRP assay by using a magnetic permeability detector has been reported with a detection limit of 0.2 mg/l (Kriz et al, 2005). A label-free assay using surface plasmon resonance (SPR)-based technology was demonstrated with a detection limit of 2-5 mg/l (Meyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%